2021
DOI: 10.1002/ange.202011144
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable Aqueous Aluminum Organic Batteries

Abstract: Aqueous aluminum‐ion batteries (AABs) are regarded as promising next‐generation energy storage devices, and the current reported cathodes for AABs mainly focused on inorganic materials which usually implement a typical Al3+ ions (de)insertion mechanism. However, the strong electrostatic forces between Al3+ and the host materials usually lead to sluggish kinetics, poor reversibility and inferior cycling stability. Herein, we employ an organic compound with redox‐active moieties, phenazine (PZ), as the cathode m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Chen et al . prove that this electrolyte is also suitable to couple with organic cathode materials [21] . They found that the battery shows the best performance in the 5 M Al(OTF) 3 electrolyte as compared to those in 0.5, 1 and 3 M electrolytes.…”
Section: Design Strategies For Al Metal Anodementioning
confidence: 95%
See 3 more Smart Citations
“…Chen et al . prove that this electrolyte is also suitable to couple with organic cathode materials [21] . They found that the battery shows the best performance in the 5 M Al(OTF) 3 electrolyte as compared to those in 0.5, 1 and 3 M electrolytes.…”
Section: Design Strategies For Al Metal Anodementioning
confidence: 95%
“…Chen et al prove that this electrolyte is also suitable to couple with organic cathode materials. [21] They found that the battery shows the best performance in the 5 M Al(OTF) 3 electrolyte as compared to those in 0.5, 1 and 3 M electrolytes. This is because an Al 3 + (OTF À ) a solvation structure can be formed when increasing electrolyte concentration.…”
Section: Electrolyte Concentrationmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the current non-aqueous halides ionic liquid electrolytes of high cost, severe corrosivity, air sensitivity, and environmental concerns have significantly restricted their practical applications [1][2][3] . In contrast, aqueous electrolytes with features of higher safety, lower cost, H2O/O2 insensitivity, and easier fabrication has attracted remarkable attention [4][5][6] . Among such battery prototype, manganese oxides with layered structure and high energy density are widely employed as the positive electrode materials for assembling aqueous aluminum ion batteries (AAIBs).…”
Section: Introductionmentioning
confidence: 99%